Randomised clinical trial of cryoballoon versus irrigated radio frequency catheter ablation for atrial fibrillation—the effect of double short versus standard exposure cryoablation duration during pulmonary vein isolation (CIRCA-DOSE): methods and rationale. Issue 10 (5th October 2017) - Andrade, Jason G; Deyell, Marc W; Badra, Mariano; Champagne, Jean; Dubuc, Marc; Leong-Sit, Peter; Macle, Laurent; Novak, Paul; Roux, Jean-Francois; Sapp, John; Tang, Anthony; Verma, Atul; et al.
Abstract : Introduction: Pulmonary vein isolation (PVI) is an effective therapy for paroxysmal atrial fibrillation (AF), but it has limitations. The two most significant recent advances have centred on the integration of real-time quantitative assessment of catheter contact force into focal radio frequency (RF) ablation catheters and the development of dedicated ablation tools capable of achieving PVI with a single ablation lesion (Arctic Front cryoballoon, Medtronic, Minneapolis, MN, USA). Although each of these holds promise for improving the clinical success of catheter ablation of AF, there has not been a rigorous comparison of these advanced ablation technologies. Moreover, the optimal duration of cryoablation (freezing time) has not been determined. Methods and analysis: Patients undergoing an initial PVI procedure for paroxysmal AF will be recruited. Patients will be randomised 1:1:1 between contact-force irrigated RF ablation, short duration cryoballoon ablation (2 min applications) and standard duration cryoballoon ablation (4 min applications). The primary outcome is time to first documented AF recurrence on implantable loop recorder. With a sample size of 111 per group and a two-sided 0.025 significance level (to account for the two main comparisons), the study will have 80% power (using a log-rank test) to detect a difference of 20% between contact force RF catheter ablation and either of the two cryoballoon ablation groups. Factoring in a 4% loss to follow-up, 116 patients per group should be randomised and followed for a year (total study population of 348). Ethics and dissemination: The study was approved by the University of British Columbia Office of Research (Services) Ethics Clinical Research Ethics Board. Results of the study will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT01913522; Pre-results